Small-scale mapping of selected soils area in UiTM Jasin, Melaka using the Geospatial Information System (GIS) and field sampling techniques / Muhammad Naim Khairuddin - Khairuddin, Muhammad Naim (Faculty of Plantation and Agrotechnology, 2019)
In most of the agricultural area, the efficient and proper management is found effectives using the information gained from the combination of Geospatial Information System (GIS) and field sampling techniques. To familiarize the techniques aligned with recent technology, this study aimed to determine the physico-chemical properties of selected soils area in UiTM Jasin Melaka and to develop a small-scale mapping using the arcgis software. The field results showed that the soil ph range between ph 4.2 and ph 5.2 with a bulk density range between 0.31gcm-3 to 0.64gcm-3. The area also has high soil moisture contents and consists of mixtures of organic matter which has undergo complete decomposition. The thematic map developed from the field data was displayed in different colors to differentiate between parameters. It is suggested that the GIS techniques combine with the field sampling to manage the land is much easier for a proper land management.